Implementation of Fisherman Insurance Assistance Program in South Buton Regency, Southeast Sulawesi Province - La Ode Yusran Syarif; Sarwono Sarwono; Imam Hanafi (Wacana Journal of Social and Humanity Studies, 2019)
In the policy of Maritime and Fisheries Ministry No. 18/2016 on Insurance Protection of Risk for Fisherman, Fish Cultivator, and Salt Farmer is presented in a program in the form of Fisherman Insurance Premium Assistance carried out by the Directorate General of Capture Fishery and Regency/Municipal Maritime and Fisheries Agency all over Indonesia, one of which is South Buton Regency Maritime and Fisheries Agency which becomes the object of this research. Fisherman Insurance Premium Assistance Program is a program to protect small and traditional fishermen. The research used was qualitative method aiming to describe the implementation of Fisherman Insurance Premium Assistance Program and then it was analyzed using Edward III implementation model. The findings showed that the program implementation had not run well resulted from the factors, such as the Socialization carried out by South Buton Maritime and Fisheries Agency had not been maximal, the limitedness of either staff resources or budgeting, and there was no fishermen data update with the result that in data validation process a great number of benefit receiver candidates who had registered could not be proposed to receive this program.Â Â